Optimal aspirin dose in acute coronary syndromes: an emerging consensus. (March 2014) - DiNicolantonio, James J; Norgard, Nicholas B; Meier, Pascal; Lavie, Carl J; O'Keefe, James H; Niazi, Asfandyar K; Chatterjee, Saurav; Packard, Kathleen A; D'Ascenzo, Fabrizio; Cerrato, Enrico; Biondi-Zoccai, Giuseppe; Bangalore, Sripal; et al.
ABSTRACT: : Numerous clinical trials testing the efficacy of aspirin for the secondary prevention of cardiovascular disease have been published. We reviewed the literature pertaining to aspirin dose in acute coronary syndrome patients. Clinical trials assessing the comparative efficacy of different doses of aspirin are scarce. This complex antiplatelet therapy landscape makes it difficult to identify the best aspirin dose for optimizing efficacy and minimizing risk of adverse events, while complying with the various guidelines and recommendations. Despite this fact, current evidence suggests that aspirin doses of 75–100 mg/day may offer the optimal benefit:risk ratio in acute coronary syndrome patients.